2020
DOI: 10.1097/qai.0000000000002508
|View full text |Cite
|
Sign up to set email alerts
|

Improved Viral Suppression With Streamlined Care in the SEARCH Study

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…32 Our findings add to the evidence demonstrating that the population health benefits gained by the SEARCH intervention extend to PWH reporting hazardous alcohol use, adding to the previously identified groups at high risk for poor HIV care outcomes, including pregnant and postpartum women, 33 men with low CD4 counts, 34 and treatment experienced patients with viremia. 28…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 Our findings add to the evidence demonstrating that the population health benefits gained by the SEARCH intervention extend to PWH reporting hazardous alcohol use, adding to the previously identified groups at high risk for poor HIV care outcomes, including pregnant and postpartum women, 33 men with low CD4 counts, 34 and treatment experienced patients with viremia. 28…”
Section: Discussionmentioning
confidence: 99%
“…32 Our findings add to the evidence demonstrating that the population health benefits gained by the SEARCH intervention extend to PWH reporting hazardous alcohol use, adding to the previously identified groups at high risk for poor HIV care outcomes, including pregnant and postpartum women, 33 men with low CD4 counts, 34 and treatment experienced patients with viremia. 28 There are several potential mechanisms for how the SEARCH intervention achieved a higher prevalence of ART uptake and viral suppression among PWH reporting hazardous alcohol use compared with control. First, and perhaps most importantly, patient-centered care focused on decreasing structural barriers, increasing care flexibility (ie, allowing extended clinic hours, late arrivals, and appointment flexibility), improving patient-clinician relationships, and enhancing patient and physician HIV/ART knowledge, which have been shown to predict retention in care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of this population-wide screening, offered in both randomized arms at baseline, we found that a patient-centered chronic care delivery model improved hypertension control and reduced mortality among adults with uncontrolled hypertension beyond that of optimized standard care. We previously reported profound population-level health effects of this care delivery model among HIV-infected persons, including reduced mortality among those with prevalent HIV infection [ 17 ] and men with low CD4 counts [ 30 ], improved viral suppression among those with HIV viremia despite prior attempts at care engagement [ 31 ], reduced maternal-to-child transmission of HIV [ 32 ], and decreased incidence of tuberculosis [ 17 ]. Taken together, our findings support the value of integrated patient-centered chronic care models, when combined with multidisease community-based screening programs, for improving a wide range of population health outcomes.…”
Section: Discussionmentioning
confidence: 99%